2015
DOI: 10.1111/apm.12406
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic role of procalcitonin (PCT) and MR‐pro‐Adrenomedullin (MR‐proADM) in bacterial infections

Abstract: Rapid diagnosis of bacterial infections is crucial for adequate antibiotic treatment. Serum molecules such as Procalcitonin (PCT) have been used as biomarkers of infection. Recently, the mid-regional pro-Adrenomedullin (MR-proADM) has been evaluated in combination with PCT for sepsis diagnosis. The diagnostic role of PCT and MR-proADM both in sepsis and in localized infections together with their contribution to effective antibiotic therapy has been evaluated. One hundred and eighty-two patients with bacterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 36 publications
6
53
0
1
Order By: Relevance
“…A diagnostic index with good sensitivity and specificity is highly essential in clinical settings to detect intracranial infection and guide clinicians to take necessary interventions, improve the prognosis of patients, and reduce the hospitalization time and economic burden. PCT has been widely studied in recent years for the early diagnosis of bacterial infection severity, treatment effect, disease prognosis and as reference for antibiotic use (24 26). …”
Section: Discussionmentioning
confidence: 99%
“…A diagnostic index with good sensitivity and specificity is highly essential in clinical settings to detect intracranial infection and guide clinicians to take necessary interventions, improve the prognosis of patients, and reduce the hospitalization time and economic burden. PCT has been widely studied in recent years for the early diagnosis of bacterial infection severity, treatment effect, disease prognosis and as reference for antibiotic use (24 26). …”
Section: Discussionmentioning
confidence: 99%
“…In a landmark study of Angeletti et al[42] level of PCT and mid-regional pro-adrenomedullin (MR-proADM) were found to be significantly higher in patients with sepsis caused by Gram-negative than Gram-positive strains. These data are also confirmed by other studies[43-45].…”
Section: Discussionmentioning
confidence: 99%
“…Angeletti et al (66) studied the behavior of PCT and MR-proADM at income and evolutionarily biomarkers in a group of patients with sepsis and one with localized infection. They evaluated the diagnostic capacity, response to antibiotics and prognostic value of these biomarkers individually and combined.…”
Section: Utility Of Pct and Mr-proadm Combined In The Diagnosis And Pmentioning
confidence: 99%